2013
DOI: 10.1073/pnas.1304231110
|View full text |Cite
|
Sign up to set email alerts
|

Prereplicative repair of oxidized bases in the human genome is mediated by NEIL1 DNA glycosylase together with replication proteins

Abstract: Base oxidation by endogenous and environmentally induced reactive oxygen species preferentially occurs in replicating single-stranded templates in mammalian genomes, warranting prereplicative repair of the mutagenic base lesions. It is not clear how such lesions (which, unlike bulky adducts, do not block replication) are recognized for repair. Furthermore, strand breaks caused by base excision from ssDNA by DNA glycosylases, including Nei-like (NEIL) 1, would generate double-strand breaks during replication, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
133
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 65 publications
6
133
0
Order By: Relevance
“…This inhibition should be essential in vivo for preventing double strand break formation (5,13). To further understand the function of NEIL1 in the replicating genome, we recently provided direct experimental evidence for the "cow-catcher" role of NEIL1 in prereplicative repair of oxidized DNA bases in the template strand (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This inhibition should be essential in vivo for preventing double strand break formation (5,13). To further understand the function of NEIL1 in the replicating genome, we recently provided direct experimental evidence for the "cow-catcher" role of NEIL1 in prereplicative repair of oxidized DNA bases in the template strand (5).…”
mentioning
confidence: 99%
“…We have previously shown that replication protein A, a mammalian ssDNA-binding protein essential for DNA replication, inhibits DNA glycosylase activity of NEIL1/NEIL2 in vitro with the replication fork-mimicking primer-template DNA substrate (13). This inhibition should be essential in vivo for preventing double strand break formation (5,13). To further understand the function of NEIL1 in the replicating genome, we recently provided direct experimental evidence for the "cow-catcher" role of NEIL1 in prereplicative repair of oxidized DNA bases in the template strand (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The N terminus contains the glycosylase domain of NEIL1, and the C terminus is intrinsically disordered (8,11). Whereas the C terminus is dispensable for both glycosylase and lyase activities in vitro, it interacts with many proteins in vivo and is required for efficient DNA repair activity inside the cells (12,13). NEIL1 is also unique among the three human NEIL proteins in that it is increased in an S-phase-specific manner and carries out prereplicative repair of oxidized bases in the human genome (8,12).…”
mentioning
confidence: 99%
“…Whereas the C terminus is dispensable for both glycosylase and lyase activities in vitro, it interacts with many proteins in vivo and is required for efficient DNA repair activity inside the cells (12,13). NEIL1 is also unique among the three human NEIL proteins in that it is increased in an S-phase-specific manner and carries out prereplicative repair of oxidized bases in the human genome (8,12). Moreover, increasing literature has further emphasized the importance of NEIL1's cellular repair activity, as NEIL1 deficiency has led to multiple abnormalities and is associated with severe human diseases, including cancer (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%